Effect of dapagliflozin according to baseline systolic blood pressure in the Dapagliflozin and Prevention of Adverse Outcomes in Heart Failure trial (DAPA-HF). (21st August 2020) - Serenelli, Matteo; Böhm, Michael; Inzucchi, Silvio E; Køber, Lars; Kosiborod, Mikhail N; Martinez, Felipe A; Ponikowski, Piotr; Sabatine, Marc S; Solomon, Scott D; DeMets, David L; Bengtsson, Olof; Sjöstrand, Mikaela; et al.
Abstract: Aims: Concern about hypotension often leads to withholding of beneficial therapy in patients with heart failure and reduced ejection fraction (HFrEF). We evaluated the efficacy and safety of dapagliflozin, which lowers systolic blood pressure (SBP), according to baseline SBP in Dapagliflozin and Prevention of Adverse Outcomes in Heart Failure trial (DAPA-HF). Methods and results: Key inclusion criteria were: New York Heart Association Class II−IV, left ventricular ejection fraction ≤ 40%, elevated N-terminal pro-B-type natriuretic peptide level, and SBP ≥95 mmHg. The primary outcome was a composite of worsening heart failure or cardiovascular death. The efficacy and safety of dapagliflozin were examined using SBP as both a categorical and continuous variable. A total of 1205 patients had a baseline SBP <110 mmHg; 981 ≥ 110 < 120; 1149 ≥ 120 < 130; and 1409 ≥ 130 mmHg. The placebo-corrected reduction in SBP from baseline to 2 weeks with dapagliflozin was −2.54 (−3.33 to −1.76) mmHg ( P  < 0.001), with a smaller between-treatment difference in patients in the lowest compared to highest SBP category. Patients in the lowest SBP category had a much higher rate (per 100 person-years) of the primary outcome [20.6, 95% confidence interval (95% CI) 17.6–24.2] than those in the highest SBP category (13.8, 11.7–16.4). The benefit and safety of dapagliflozin was consistent across the range of SBP; hazard ratio (95% CI) in each SBP group, lowest to highest: 0.76 (0.60–0.97), 0.76 (0.57–1.02), 0.81 (0.61–1.08), and 0.67 (0.51–0.87), P interaction = 0.78. Study drug discontinuation did not differ between dapagliflozin and placebo across the SBP categories examined. Conclusion: Dapagliflozin had a small effect on SBP in patients with HFrEF and was superior to placebo in improving outcomes, and well tolerated, across the range of SBP included in DAPA-HF. Clinical Trial Registration: ClinicalTrials.gov NCT03036124. Graphical Abstract: